A Loosely Self-stabilizing Protocol for Randomized Congestion Control with Logarithmic Memory - Feldmann, Michael; Götte, Thorsten; Scheideler, Christian (Proceedings of the 21st International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We consider congestion control in peer-to-peer distributed systems. The problem can be reduced to the following scenario: Consider a set $V$ of $n$ peers (called \emph{clients} in this paper) that want to send messages to a fixed common peer (called \emph{server} in this paper). We assume that each client $v \in V$ sends a message with probability $p(v) \in [0,1)$ and the server has a capacity of $\sigma \in \mathbb{N}$, i.e., it can recieve at most $\sigma$ messages per round and excess messages are dropped. The server can modify these probabilities when clients send messages. Ideally, we wish to converge to a state with $\sum p(v) = \sigma$ and $p(v) = p(w)$ for all $v,w \in V$. We propose a \emph{loosely} self-stabilizing protocol with a slightly relaxed legitimate state. Our protocol lets the system converge from \emph{any} initial state to a state where $\sum p(v) \in \left[\sigma \pm \epsilon\right]$ and $|p(v)-p(w)| \in O(\frac{1}{n})$. This property is then maintained for $\Omega(n^{\mathfrak{c}})$ rounds in expectation. In particular, the initial client probabilities and server variables are not necessarily well-defined, i.e., they may have arbitrary values. Our protocol uses only $O(W + \log n)$ bits of memory where $W$ is length of node identifiers, making it very lightweight. Finally we state a lower bound on the convergence time an see that our protocol performs asymptotically optimal (up to some polylogarithmic factor).

Stepwise Growth of Ruthenium Terpyridine Complexes on Au Surfaces - Peter, Sophia Katharina; Kaulen, Corinna; Hoffmann, Alexander; Ogieglo, Wojciech; Karthäuser, Silvia; Homberger, Melanie; Herres-Pawlis, Sonja; Simon, Ulrich (The Journal of Physical Chemistry C)

New Kids in Lactide Polymerization: Highly Active and Robust Iron Guanidine Complexes as Superior Catalysts - Rittinghaus, Ruth D.; Schäfer, Pascal M.; Albrecht, Pascal; Conrads, Christian; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka N.; Bienemann, Olga; Pich, Andrij; Herres-Pawlis, Sonja (ChemSusChem)
Abstract Polylactide is a biodegradable versatile material based on annually renewable resources and thus CO2-neutral in its lifecycle. Until now, tin(II)octanoate [Sn(Oct2)] was used as catalyst for the industrial ring-opening polymerization of lactide in spite of its cytotoxicity. On the way towards a sustainable catalyst, three iron(II) hybrid guanidine complexes were investigated concerning their molecular structure and applied to the ring-opening polymerization of lactide. The complexes could polymerize unpurified technical-grade rac-lactide as well as recrystallized l-lactide to long-chain polylactide in bulk with monomer/initiator ratios of more than 5000:1 in a controlled manner following the coordination–insertion mechanism. For the first time, a biocompatible complex has surpassed Sn(Oct)2 in its polymerization activity under industrially relevant conditions.
Keywords: bioplastics; guanidines; iron; lactide; ring-opening polymerization

Thermodynamic speed of sound of xenon - Javed, Muhammad Ali; Baumhögger, Elmar; Vrabec, Jadran (The Journal of Chemical Thermodynamics)

Properties of Co-Evaporated RbInSe2 Thin Films - Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Bertram, Tobias; Maticiuc, Natalia; Yetkin, Hasan A; Gunder, René; Schlatmann, Rutger; Kühne, Thomas D; Kaufmann, Christian A; Mirhosseini, Hossein (physica status solidi (RRL)--Rapid Research Letters)

Opposing Electronic and Nuclear Quantum Effects on Hydrogen Bonds in H2O and D2O - Clark, Timothy; Heske, Julian Joachim; Kühne, Thomas (ChemPhysChem)
Abstract The effect of extending the O−H bond length(s) in water on the hydrogen-bonding strength has been investigated using static ab initio molecular orbital calculations. The “polar flattening” effect that causes a slight σ-hole to form on hydrogen atoms is strengthened when the bond is stretched, so that the σ-hole becomes more positive and hydrogen bonding stronger. In opposition to this electronic effect, path-integral ab initio molecular-dynamics simulations show that the nuclear quantum effect weakens the hydrogen bond in the water dimer. Thus, static electronic effects strengthen the hydrogen bond in H2O relative to D2O, whereas nuclear quantum effects weaken it. These quantum fluctuations are stronger for the water dimer than in bulk water.
Keywords: ab initio calculations; bond theory; hydrogen bonds; isotope effects; solvent effects

Impact of intermolecular vibrational coupling effects on the sum-frequency generation spectra of the water/air interface - Kaliannan, Naveen Kumar; Henao Aristizabal, Andres; Wiebeler, Hendrik; Zysk, Frederik; Ohto, Tatsuhiko; Nagata, Yuki; D. Kühne, Thomas (Molecular Physics)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Controlling the strength of interaction between carbon dioxide and nitrogen-rich carbon materials by molecular design - Walczak, Ralf; Savateev, Aleksandr; Heske, Julian Joachim; Tarakina, Nadezda V.; Sahoo, Sudhir; Epping, Jan D.; Kühne, Thomas; Kurpil, Bogdan; Antonietti, Markus; Oschatz, Martin (Sustainable Energy Fuels)
Thermal treatment of hexaazatriphenylene-hexacarbonitrile (HAT-CN) in the temperature range from 500 °C to 700 °C leads to precise control over the degree of condensation{,} and thus atomic construction and porosity of the resulting C2N-type materials. Depending on the condensation temperature of HAT-CN{,} nitrogen contents of more than 30 at% can be reached. In general{,} these carbons show adsorption properties which are comparable to those known for zeolites but their pore size can be adjusted over a wider range. At condensation temperatures of 525 °C and below{,} the uptake of nitrogen gas remains negligible due to size exclusion{,} but the internal pores are large and polarizing enough that CO2 can still adsorb on part of the internal surface. This leads to surprisingly high CO2 adsorption capacities and isosteric heat of adsorption of up to 52 kJ mol−1. Theoretical calculations show that this high binding enthalpy arises from collective stabilization effects from the nitrogen atoms in the C2N layers surrounding the carbon atom in the CO2 molecule and from the electron acceptor properties of the carbon atoms from C2N which are in close proximity to the oxygen atoms in CO2. A true CO2 molecular sieving effect is achieved for the first time in such a metal-free organic material with zeolite-like properties{,} showing an IAST CO2/N2 selectivity of up to 121 at 298 K and a N2/CO2 ratio of 90/10 without notable changes in the CO2 adsorption properities over 80 cycles.

Enhancement of the asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Scientific Reports)

A Branch and Bound Approach for Large Pre-Marshalling Problems - Tanaka, Shunji; Tierney, Kevin; Parreño-Torres, Consuelo; Alvarez-Valdes, Ramon; Ruiz, Rubén (European Journal of Operational Research)

Hyper-Reactive Tabu Search for MaxSAT - Ansótegui, Carlos; Heymann, Britta; Pon, Josep; Sellmann, Meinolf; Tierney, Kevin (Learning and Intelligent Optimization)

Specifying Web Interfaces for Command-line Applications Based on OpenAPI - Wolters, Dennis; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing – ICSOC 2019 Workshops)

Diffusion of Methane in Supercritical Carbon Dioxide Across the Widom Line - Guevara-Carrion, Gabriela; Ancherbak, Sergiy; Mialdun, Aliaksandr; Vrabec, Jadran; Shevtsova, Valentina (Scientific Reports)

All-neural Online Source Separation, Counting, and Diarization for Meeting Analysis - von Neumann, Thilo; Kinoshita, Keisuke; Delcroix, Marc; Araki, Shoko; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2019, Brighton, UK)
Automatic meeting analysis comprises the tasks of speaker counting, speaker diarization, and the separation of overlapped speech, followed by automatic speech recognition. This all has to be carried out on arbitrarily long sessions and, ideally, in an online or block-online manner. While significant progress has been made on individual tasks, this paper presents for the first time an all-neural approach to simultaneous speaker counting, diarization and source separation. The NN-based estimator operates in a block-online fashion and tracks speakers even if they remain silent for a number of time blocks, thus learning a stable output order for the separated sources. The neural network is recurrent over time as well as over the number of sources. The simulation experiments show that state of the art separation performance is achieved, while at the same time delivering good diarization and source counting results. It even generalizes well to an unseen large number of blocks.

Diffusion Limited Evaporation of a Binary Liquid Film - Chatwell, René Spencer; Heinen, Matthias; Vrabec, Jadran (International Journal of Heat and Mass Transfer)

Kirkwood-Buff Integration: A Promising Route to Entropic Properties? - Fingerhut, Robin; Vrabec, Jadran (Fluid Phase Equilibria)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

"Producing Cloud-Native": Smart Manufacturing Use Cases on Kubernetes - Schneider, Stefan Balthasar; Peuster, Manuel; Hannemann, Kai; Behnke, Daniel; Müller, Marcel; Bök, Patrick-Benjamin; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN) Demo Track)
Building on 5G and network function virtualization (NFV), smart manufacturing has the potential to drastically increase productivity, reduce cost, and introduce novel, flexible manufacturing services. Current work mostly focuses on high-level scenarios or emulation-based prototype deployments. Extending our previous work, we showcase one of the first cloud-native 5G verticals focusing on the deployment of smart manufacturing use cases on production infrastructure. In particular, we use the 5GTANGO service platform to deploy our developed network services on Kubernetes. For this demo, we implemented a series of cloud-native virtualized network functions (VNFs) and created suitable service descriptors. Their light-weight, stateless deployment on Kubernetes enables quick instantiation, scalability, and robustness.
Keywords: 5G; NFV; Smart Manufacturing; Cloud-Native; Kubernetes

Investigation of Near-Surface Defects of Nanodiamonds by High-Frequency EPR and DFT Calculation - Cho, F. H.; Peng, Z.; Biktagirov, T.; Gerstmann, Uwe; Takahashi, S. (The Journal of Chemical Physics)